Optimal Deteriorating Inventory Models for Varies Supply Life Cycles - Gede A Widyadana; Kun Jen Wang; Nyoman Sutapa (International Journal of Supply Chain Management, 2020)
Agriculture items, such as fruits and vegetables, have different supply and demand characteristics during a harvest period. Fruits supply in the first and end of harvest time are not reliable so sometimes supply are not available when needed. Fruits demand is different during harvest season. In the first harvest season, demand depends on price and at the end of harvest time, the demand depends on presentation of the items. In this study, inventory deteriorating items models for the first and the end of the harvest season are developed. Since closed-form solutions cannot be derived from the models, a Genetic Algorithm and a heuristic method are used to solve the problems. A numerical example and sensitivity analysis are conducted to illustrate the model and get insights. The sensitivity analysis shows that the supplier will increase his price when supply is not reliable at the early harvest period.Â  The results show that the unreliable supply is susceptible to the total cost at the end of the harvest period.